Arabic Language Acculturation in the Jama’ah Tabligh Community of Cot Goh Aceh Besar : Taṡaqquf al-Lughah al-‘Arabiyyah fī Mujtama‘ Jamā‘ah at-Tablīgh bi Cot Goh Aceh Besar - Kurnia Damanik; Nurchalis; Sumardi; Zulkhairi (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study examines the cultural acculturation that occurs within the Jama’ah Tabligh community of Cot Goh, Aceh Besar, particularly focusing on the blending of languages within a social group. The study covers aspects such as forms of address, naming practices, and communication patterns. At this stage, acculturation results in the emergence of a new cultural synthesis without eliminating the original cultural identity. This process generates new ideas across various aspects, including language, social life, culture, parenting patterns, and education, in which two different elements interact and become intertwined in everyday life. The purpose of this study is to reveal the process of linguistic acculturation as well as the terms used by the Jama’ah Tabligh of Cot Goh, in order to understand the outcomes of language acculturation within this community. The theoretical framework applied in this study is the Cultural Acculturation Theory proposed by John W. Berry. The research employs a qualitative descriptive method, in which data are described in accordance with the ongoing processes of cultural acculturation. This study also explores attitudes, tensions, relationships, and perspectives that emerge within a particular social setting. Based on the findings of field research conducted on May 10th, 11th, and 12th, 2025, using interview and observation methods with members of the Jama’ah Tabligh of Cot Goh, it was found that several Arabic terms such as ta‘līm (تَعْلِيم), bayān (بَيَان), and mushāwarah (مُشَاوَرَة) are commonly used in the activities of the Jama’ah Tabligh of Cot Goh. These linguistic practices have a positive influence, particularly in socio-religious and cultural aspects, contributing to significant changes among the community members. تتناول هذه الدراسة ظاهرةَ التثاقف الثقافي التي تحدث داخل جماعة الدعوة والتبليغ في كوت غوه، آتشيه الكبرى، ولا سيما ما يتعلق بامتزاج اللغات داخل الجماعة الاجتماعية، بما يشمل جوانب مثل أساليب النداء، والتسمية، وأنماط التواصل. وتُسفر هذه المرحلة من التثاقف عن نشوء مزيج ثقافي جديد دون إلغاء الهوية الثقافية الأصلية. كما ينتج عن هذا التثاقف أفكار جديدة في مجالات متعددة، مثل اللغة، والحياة الاجتماعية، والثقافة، وأنماط التربية، والتعليم، حيث تتفاعل عنصران مختلفان ويتداخلان في الحياة اليومية. وتهدف هذه الدراسة إلى الكشف عن التثاقف اللغوي والمصطلحات المستخدمة لدى جماعة الدعوة والتبليغ في كوت غوه، بما يسهم في فهم نتائج التثاقف اللغوي داخل هذه الجماعة. وتعتمد الدراسة على نظرية التثاقف الثقافي التي قدّمها جون و. بيري (John W. Berry). وتستخدم هذه الدراسة المنهج الوصفي النوعي، حيث تقوم بوصف البيانات المتوافرة والمتزامنة مع عملية التثاقف الثقافي الجارية، كما تكشف عن المواقف، والتباينات، والعلاقات، ووجهات النظر التي تظهر ضمن إطار اجتماعي معيّن. واستنادًا إلى نتائج البحث الميداني الذي أُجري في الفترة من 10 إلى 12 مايو 2025، باستخدام أسلوبي المقابلة والملاحظة مع أعضاء جماعة الدعوة والتبليغ في كوت غوه، تبيّن وجود عدد من المصطلحات العربية مثل تعليم، وبيان، ومشاورة تُستخدم في أنشطة الجماعة، إلى جانب تأثيرات إيجابية، لا سيما في الجوانب الاجتماعية والدينية والثقافية، مما أسهم في إحداث تغيّرات ملموسة لدى أفراد الجماعة.. Penelitian ini mengkaji akulturasi budaya yang terjadi pada jama’ah tabligh cot goh aceh besar mencakup percampuran bahasa yang terjadi dalam suatu kelompok, meliputi aspek-aspek seperti sapaan, penamaan dan komunikasi. Pada tahapan ini menghasilkan perpaduan budaya yang baru tanpa menghilangkan identitas budaya asli. Yang mana pada akulturasi ini menghasilkan gagasan baru dalam berbagai aspek seperti, bahasa, sosial, budaya, pola asuh dan pendidikan dimana dua unsur yang berbeda saling berinteraksi dan terjalin dalam kehidupan sehari-hari.Tujuan dari penelitian ini adalah untuk mengungkap akulturasi bahasa serta Istilah-Istilah yang digunakan oleh Jama’ah Tabligh Cot Goh, sehingga kita dapat memahami hasil Akulturasi Bahasa yang terjadi di dalam komunitas tersebut. Adapun pendekatan teori yang di gunakan adalah Teori Akulturasi Budaya yang dikemukakan oleh John W. Berry.Metode penelitian yang digunakan adalah Metode Deskriptif Kualitatif penelitian ini menguraikan data yang ada bersamaan dengan yang sedang terjadi dalam Akulturasi Budaya,penelitian ini juga mengungkapkan sikap,pertentangan,hubungan serta pandangan yang terjadi dalam sebuah lingkup. Berdasarkan hasil penelitian pada tanggal 10,11 hingga 12 mei 2025 dengan metode wawancara dan observasi jamaah Tabligh Cot Goh. Bahwa adanya beberapa istilah Bahasa Arab seperti تَعْلِيم, بَيَان, مُشَاوَرَة yang digunakan dalam kegiatan Jama’ah Tabligh Cot Goh serta pengaruh positif terutama terhadap masalah sosial keagamaan dan budaya yang memberikan perubahan yang signifikan kepada para jama’ah nya.